Attitudes of Young Adult Men Toward Domestic Violence and Factors Affecting Their Attitudes in Turkey. Issue 18 (September 2019) - Adıbelli, Derya; Ünal, Ayşe Sevim; Şen, Tülay
Domestic violence is commonly observed worldwide; however, exposure to violence is not often mentioned directly. Prevention of domestic violence may be one of the most important social problems and requires much time and effort to resolve. This study was conducted to determine the attitudes toward domestic violence of Turkish males who are young adult and undertake military service, and the factors that affect these attitudes. A cross-sectional study design was used. This study was conducted with 221 young adult men who applied to Sarıkamış Military Hospital between December 2012 and February 2013. A questionnaire and the Attitude Toward Domestic Violence Scale were used for the collection of data. One-way ANOVA, T test, Kruskal–Wallis test, and Mann–Whitney U test were used in the process of analyzing the data. In the study, it was found that 10% of the young adult men were exposed to violence within their own family and the average of their total scores from the Attitude Toward Domestic Violence Scale was 49.41 ± 7.27. It was confirmed that undereducated men have more negative attitudes toward domestic violence than other groups. The present study determined that men who have negative attitudes toward domestic violence and who have a low education level affected attitudes toward domestic violence negatively. It is important that violence is prevented before it occurs. In this respect, health professionals, politicians, teachers, academics, and all community leaders have an important role in preventing initiatives on violence.